Teknik Persuasif dalam Buku Jangan Mau Jadi Orang Rata-Rata Karya Ahmadi Rifa’i Rif’an - Vira Shinthya, Ade; Supriyadi, Supriyadi (UIR PRESS, 2021)
This research is entitled Persuasive Techniques in Book Don’t Want to Be Average People by Ahmad Rifa’i Rif’an. This research is motivated by the existence of several persuasive techniques in the book Persuasive Techniques in the book Don’t Want to Be an Average Person which influences the reader. Research problem: how are persuasive techniques rationalization, identification, suggestion, replacement, projection in the book Don’t Want to Be an Average Person Ahmad Rifa’i Rif’an?. The porpose of this study: to describe, analyze, and interpret persuasive techniques rationalization, identification, suggestion, conformity, compensation, replacement, projections in the book Don’t to be an Average Person by Ahmad Rifa’i Rif’an. This study uses the theory of Goris Keraf 2007, using the content analysis method. The data collection techniques and hermeneutic techniques. The data analysis technicque used is coding or coding, classification, and interpretation. The results of research on persuasive techniques in the book Don’t Want to Be an Average Person by Ahmad Rifa’i Rif’am found 71 persuasive techniques which included (1) rationalization there were 26 data, (2) identification there were 18 data, (3) suggestions there are 24 data, (4) conformitay contains 1 data, (5) compensation contains 1 data, (6) replacement contains 1 data, (7) projections contains no data. So, it can be concluded that the persuasive techniques used by Ahmad Rifa’i Rif’an in the book Don’t Want to Be an Average Person are more dominant using rationalization persuasive techniques because they tend to provide just ification in the from of logical facts to influence readers, followed by suggestion, identification, conformity, compensation, replacement, and projection.